Interfacial engineering for high performance organic photovoltaics. Issue 3 (April 2016) - Yi, Chao; Hu, Xiaowen; Gong, Xiong; Elzatahry, Ahmed
Abstract : In the past two decades, bulk heterojunction (BHJ) organic photovoltaics (OPVs) have gained tremendous attention due to its intrinsic merits of cheap, flexible, clean and high throughput manufacturing processibility and its advanced features of short payback time. Various methodologies have been developed to approach OPVs with high power conversion efficiencies (PCEs) and long-term stability. Interfacial engineering is a proven efficient approach to achieve OPVs with high PCEs. In this article, we provide a basic overview on the recent progress of the materials, in particular, water/alcohol soluble organic materials, used as interfacial layer (IFLs) in engineering of BHJ OPVs with high PCEs. Underlying device physics of interfacial engineering and the origins of enhanced PCEs of OPVs by IFLs are highlighted.